2007
DOI: 10.1007/s11251-007-9017-6
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual change through vicarious learning in an authentic physics setting

Abstract: Recent research on principles of best practice for designing effective multimedia instruction has rarely taken into account students' alternative conceptions, which are known to strongly influence learning. The goal of this study was to determine how well students of quantum mechanics could learn 'vicariously' by watching a student-tutor dialogue based on alternative conceptions. Two video treatments were created to summarize key aspects of quantum tunneling, a fundamental quantum mechanical phenomenon. One vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 25 publications
2
32
0
1
Order By: Relevance
“…The results from both studies showed that the observers of dialoguevideos learned significantly more than the observers of monologue-videos, when the observers watched as dyads. This pattern of results (dialogue-videos being superior to monologue-videos for dyad observers) is consistent with several other studies in the literature in which the two types of videos were watched by solo observers (Craig, Driscoll & Gholson, 2004;Craig, Chi, & VanLehn, 2009;Driscoll, Craig, Gholson, Hu & Graesser, 2003;Muller, Bewes, Sharma & Reimann, 2008;Muller, Sharma, Eklund & Reimann, 2007).…”
Section: Comparing Tutorial Dialogue-videos With Lecturestyle Monologsupporting
confidence: 90%
See 1 more Smart Citation
“…The results from both studies showed that the observers of dialoguevideos learned significantly more than the observers of monologue-videos, when the observers watched as dyads. This pattern of results (dialogue-videos being superior to monologue-videos for dyad observers) is consistent with several other studies in the literature in which the two types of videos were watched by solo observers (Craig, Driscoll & Gholson, 2004;Craig, Chi, & VanLehn, 2009;Driscoll, Craig, Gholson, Hu & Graesser, 2003;Muller, Bewes, Sharma & Reimann, 2008;Muller, Sharma, Eklund & Reimann, 2007).…”
Section: Comparing Tutorial Dialogue-videos With Lecturestyle Monologsupporting
confidence: 90%
“…Similarly, Monaghan and Stenning (1998, Study 1) also showed that adult students who watched a video of a model student struggling to solve syllogism problems learned slightly more (albeit not Why conflict episodes in tutorial dialogues might enhance observers' learning has been explored in the literature by one set of investigators to explain why learning from observing tutorial dialogues is better than lecture-style monologues. The hypothesis offered in the literature is that dialogue-observers are exposed to incorrect tutee statements that are followed by their corrective refutations, and these feedback inputs provide rich information from which observing students could learn, as proposed by Muller et al, (2007Muller et al, ( , 2008. Thus, Muller et al's hypothesis is that the content of these incorrect statements, along with their refutations, provide the correct information that facilitated the observers' learning.…”
Section: Resolving Conflicts or Reacting To A Struggling Tuteementioning
confidence: 99%
“…Whether they learned from the video slices, the discussion or from both needs further exploration. What we can say though, is that students who do not talk do not necessarily switch off, which is in accordance with vicarious learning literature (see Cox et al 1999;Muller et al 2007a). Some students seemed willing just to repeat their answers from the pre-test without any extra thought to the information provided.…”
Section: Leesupporting
confidence: 87%
“…First, this student relates to the emotions of the student in the dialogue, something we have observed previously (Muller et al, 2007). Schunk and Hanson (1985) found that students who watched a peer demonstrate a particular mathematics skill displayed higher self-efficacy and performance than those who did not.…”
Section: Perceptions Of Alternative Conceptionsmentioning
confidence: 82%
“…In our previous work, we showed that a dialogue involving alternative conceptions led to higher posttest scores than a similar presentation made by a single speaker involving only correct conceptions (Muller, Bewes, Sharma, & Reimann, in press;Muller, Sharma, Eklund & Reimann, 2007). We hypothesized that the cognitive load engendered with the dialogue treatment would be greater than with the simple expository treatment, but less than with a simulation.…”
Section: Conceptual Change Research and Constructivismmentioning
confidence: 91%